Risk Factors for Malaria in Pregnant Women (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Malaria is a major worldwide contagious disease, including Indonesia, and is an important public health issue. Prevalence of malaria among pregnant women and its risk factors in Pesawaran, Lampung Province are currently unknown. This study was a cross-sectional study using rapid survey method. Data was analyzed with chi square and logistic regression. Malaria prevalence was 47.6 per mile, spread over 5 out of 11 sub-districts. One important information was the discovery of pregnant women with malaria in non-endemic districts. The result of bivariate analysis proved a relationship between knowledge and malaria with p-value 0.007 and Odds Ratio (OR) 10. Maternal behavior had p-value of 0.009, OR 9, while usage of mosquito nets had p-value of 0.01, OR 5. The multivariate analysis model formula found was Y (pregnant woman with malaria) = -7.546 + 2.353 (knowledge) + 2.270 (usage of mosquito net) + 2.250 (house condition), and pregnant woman probability of malaria 33.9%. Prevention efforts should be done through strengthening of integrated maternal class groups into malaria programs in all areas.Â